Rural and Urban Differences in Educational Placements - Richard L. Swanby (Journal of Research in Rural Education, 1988)
The purpose of this study was to compare available placements for severely handicapped students in rural and urban areas. More specifically, this study investigated the relationship of percentage of urban population to the type of placement. The data for this study were collected by a questionnaire distributed throughout the United States by a telecommunication system for special education, SpecialNet, and by direct mail. One hundred and ninety school districts from 46 states comprised the sample. As the school district names were recorded, demographic data from the National Bureau of Census were developed. The data were adjusted to identify the "percentage urban" population. Findings of the study are that severely handicapped rural students are more often placed in resource rooms while their peers from more urban districts are placed in special schools. Educational implications and suggestions for further research are presented.